1987
DOI: 10.1128/jcm.25.6.982-986.1987
|View full text |Cite
|
Sign up to set email alerts
|

Bovine milk immunoglobulins for passive immunity to infantile rotavirus gastroenteritis

Abstract: Pregnant cows were successfully hyperimmunized with all four human rotavirus serotypes, resulting in a 100-fold increase in neutralizing milk antibody titers over those of controls. Milk antibodies were isolated batchwise from 1,000 kg of pooled milk for the first 10 lactation days, yielding 10 kg of freeze-dried milk immunoglobulin concentrate consisting of 50% bovine milk immunoglobulin. Milk immunoglobulin concentrate showed neutralizing activities against all four human rotavirus serotypes that were 100 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 32 publications
1
45
1
Order By: Relevance
“…We have already reported that cow colostrum containing antibody against human rotavirus was able to prevent rotavirus infection in an orphanage (9, 10). Brussow et al (6) and Hilpert et al (16) have also reported that bovine milk concentrate containing antibody to rotavirus was able to prevent rotavirus gastroenteritis in human infants. It is expected that, in the future, active immunization with attenuated strains of rotaviruses will serve as the principal means fo.r the prevention of rotavirus gastroenteritis.…”
Section: Discussionmentioning
confidence: 98%
“…We have already reported that cow colostrum containing antibody against human rotavirus was able to prevent rotavirus infection in an orphanage (9, 10). Brussow et al (6) and Hilpert et al (16) have also reported that bovine milk concentrate containing antibody to rotavirus was able to prevent rotavirus gastroenteritis in human infants. It is expected that, in the future, active immunization with attenuated strains of rotaviruses will serve as the principal means fo.r the prevention of rotavirus gastroenteritis.…”
Section: Discussionmentioning
confidence: 98%
“…Enhanced immunity due to oral administration of immunoglobulins has been observed by a number of researchers. Feeding vaccinated cow's colostrum prevented diarrhea in infants due to infection of E. coli (Hilpert et al, 1977;Brussow et al, 1987) or rotavirus (Ebina et al, 1985) and traveler's diarrhea (Tacket et al, 1988). Oral administration of immunoglobulins from chicken egg had been used successfully by Bartz et al (1980) for the prevention of murine rotavirus infection in mice.…”
Section: Introductionmentioning
confidence: 99%
“…SEVERAL STUDIES HAVE REPORTED that the ingestion of immunoglobulins (Ig) from the colostrum of immunized cows can prevent rotavirus and enterotoxigenic Escherichia coli infection in infants and adults (Hilpert et al, 1977(Hilpert et al, , 1987Ebina et al, 1985;Briissow et al, 1987;Tacket et al, 1988). Yolken et al (1985) found Ig in raw and pasteurized milk from nonimmunized cows also had anti-rotavirus activity.…”
Section: Introductionmentioning
confidence: 99%